2016
DOI: 10.1590/2179-8087.125414
|View full text |Cite
|
Sign up to set email alerts
|

Banco de Sementes em Mina de Bauxita Restaurada no Sudeste do Brasil

Abstract: RESUMO O objetivo deste trabalho foi caracterizar o banco de sementes do solo em mina de bauxita restaurada dez anos após implantação do projeto de restauração. O estudo foi realizado em uma área onde ocorreu exploração de bauxita e posterior restauração florestal. Foram coletadas 40 amostras de solo superficial (0,25 × 0,30 × 0,05 m) para avaliação do banco de sementes pelo método de germinação em casa de sombra durante seis meses. Emergiram 2.489 plântulas, pertencentes a 69 espécies e 23 famílias botânicas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 25 publications
1
9
0
3
Order By: Relevance
“…The results of this study showed that the soil seed banks, from both areas, presented viable seeds and are composed mostly of pioneer and native seeds, that is, it is an important indicator of the recovery potential of plant communities through the natural regeneration. This pattern is common in early successional stage forests (Miranda-Neto et al, 2016;Balestrin et al, 2019;Martins et al, 2021). For example, the soil seed bank in tropical regions is mainly composed of pioneer species, light-demanding and has a higher density of seeds in the surface layers of the soil (Martins et al, 2015;Silva et al, 2021a;Martins et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of this study showed that the soil seed banks, from both areas, presented viable seeds and are composed mostly of pioneer and native seeds, that is, it is an important indicator of the recovery potential of plant communities through the natural regeneration. This pattern is common in early successional stage forests (Miranda-Neto et al, 2016;Balestrin et al, 2019;Martins et al, 2021). For example, the soil seed bank in tropical regions is mainly composed of pioneer species, light-demanding and has a higher density of seeds in the surface layers of the soil (Martins et al, 2015;Silva et al, 2021a;Martins et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the soil seed bank is essential for the maintenance of species diversity (i.e., species richness, species composition, dominance and evenness) during natural forest regeneration after disturbances (Balestrin et al, 2019;Silva et al, 2021b;Martins et al, 2021). Most of these studies on soil seed bank have focused mainly on the processes influencing the changes in community composition and species richness in disturbed areas compared to reference ecosystems (Miranda-Neto et al, 2016;Silva et al, 2019;Adjalla et al, 2022). Nevertheless, this classical approach can limit disentangling processes on plant communities during ecological restoration.…”
Section: Introductionmentioning
confidence: 99%
“…Miranda Neto et al (2017), em uma Florestal Estacional Semidecidual Montana obtiveram alta representatividade da família botânica Rubiaceae dentre as famílias encontradas no banco de sementes.…”
Section: Discussionunclassified
“…Miranda Neto et al (2017) relata que a predominância de espécies pioneiras no banco de sementes, normalmente apresentam rápido crescimento a pleno sol, é um indicador de resiliência a perturbações naturais ou antrópicas.…”
Section: Discussionunclassified
“…Muitas vezes, sequer são feitas menções sobre as espécies não arbóreas nos programas de restauração florestal e, portanto, elas sequer entram no cálculo dos índices ecológicos. No entanto, essas espécies servem de forragem para alguns herbívoros, suas flores são polinizadas por muitos insetos, seus frutos e sementes são a base alimentar de uma gama de marsupiais, roedores e pássaros, entre outras tantas funções de relevante interesse ecológico (MIRANDA et al, 2017). O fato de frutificarem mais de uma vez ao ano, as colocam até um certo ponto da restauração, como a principal fonte de alimentos para muitos dispersores (BATISTA NETO et al, 2007).…”
Section: Introductionunclassified